2007
DOI: 10.1007/s00421-007-0534-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic markers and vasodilatory capacity following acute exercise among men of differing training status

Abstract: We evaluated the effect of differing physical activity patterns on fibrinolysis and vasodilatory capacity using a cross-sectional design with 16 endurance-trained (ET) (mean+/-SE) (28+/-6 years), 14 resistance-trained (RT) (28+/-7 years), and 10 untrained (UT) (26+/-7 years) men. t-PA and PAI-1 activity and t-PA antigen were measured before and after a maximal treadmill test (VO2peak). Vasodilatory capacity was assessed using strain-gauge plethysmography on the forearm following reactive hyperemia (RH) before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…3). Although previous studies, focused on blood flow response to RH, have not paid attention to baseline blood flow [5,22,[29][30][31][32][33][34], we should emphasize that the increased RH in the COMBO group may be partly associated with an increase in baseline blood flow. The increase in baseline blood flow and RH may be induced by angiogenesis, muscular hypertrophy and improvements of endothelial and autonomic functions [5,35,36], but further study is warranted to clarify the mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“…3). Although previous studies, focused on blood flow response to RH, have not paid attention to baseline blood flow [5,22,[29][30][31][32][33][34], we should emphasize that the increased RH in the COMBO group may be partly associated with an increase in baseline blood flow. The increase in baseline blood flow and RH may be induced by angiogenesis, muscular hypertrophy and improvements of endothelial and autonomic functions [5,35,36], but further study is warranted to clarify the mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“…These results confirm the present findings and indicate that PAI-1 inhibits fibrinolysis in vivo. It suggests also that delivering PAI-1 to a forming thrombus is an important physiological mechanism for subsequent thrombus stabilization [47][48][49][50][51]. One obstacle in using wPAI-1 as a clinically useful haemostatic drug is its short half-life (2 h) [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…28 Nagelkirk et al, 29 observed that in healthy women, AREX (6 sets of 10 leg extension repetitions at 70% e 1 MR) increased fibrinolytic stimulation; however, there was no change in PAI-1 activity. Further, Baynard et al 30 examined the effect of different physical activity patterns on fibrinolysis and vasodilatory capacity using a cross-sectional design with endurance-trained, resistance-trained, and untrained men. The authors found that the trained subjects demonstrated anti-atherogenic profile, showing lower PAI-1 levels than the sedentary group.…”
Section: Discussionmentioning
confidence: 99%